Silvicultural Interventions for Maximising Water Yield: A Review of Field Experiments on Forest Hydrology - Tiwari, Rajeev Kumar (Indian Forester, 2019)
Forest reduces total runoff from a watershed due to its consumptive use. The impact of forests on stream discharge is to lower and delay the flood peaks. However, it depends upon various vegetative parameters like species, Forest cover, leaf area index, rooting zone etc. and on various watershed parameters like slope, geology, shape of watershed etc. The land use of upper catchments of major river systems in India is predominantly forest, which also receives higher rainfall. There is a lot of variation in temporal and spatial distribution of rainfall in India. Major part of the year is dry and most of the river flow during the non-monsoon period is supplemented by ground water. In view of the increasing water stress being felt in various parts of the country during non-monsoon period, intervention is required to maximize the stream discharge by manipulating the forest stand structure. Maximizing the water yield from a forested catchment requires silvicultural interventions like manipulation of species composition in favour of species with lower transpiration requirement. A preference needs to be given to species with root system, which induces higher infiltration. Various silvicultural operations like thinning, pruning, weeding etc. shall also increase the water output. The state forest departments and research organizations need to reorient the research to understand correlation of various silvicultural operations on the water yield under different forest types and densities. From Indian perspective, it is important that regulation of quality water yield is one of the objectives of forest management.